Transforming the Healthcare Revenue Cycle with Artificial Intelligence A Guide to Building Impactful AI Using Electronic Claims and Electronic Heath Record Data. - Reid, Korin (Productivity Press, 2025)
The book begins with providing an overview of key concepts such as data science, machine learning, AI, language models (such as ChatGTP) and more. Then the author expands up the defined process in the context of common revenue cycle use cases that leverage electronic claims and electronic health records.